The Revitalizing Indonesia's Religious Courts System: The Modernization Impacts and Potentials of E-Court - Dian Latifiani; Nur Arif Nugraha; Anis Widyawati; Akhmad Khalimy; Muhammad Iqbal Baiquni; Asmarani Ramli; Pratama Herry Herlambang (Unissula, 2024)
The electronic court (E-Court) system implemented in this study utilizes online technology to facilitate the legal process. This system is based on the principles of fast, simple, and low-cost, and it is designed to address the challenges of traditional court procedures. The objective of this research is to evaluate the effectiveness of E-Court implementation in the Kendal and Semarang Religious Courts in accordance with the Supreme Court Regulation No. 1 of 2019, No. 3 of 2022 and No. 7 of 2022 as well as the Directorate General of Religious Courts Agency No 5374/DJA/HM.01/X/2019, in achieving the principles of fast, simple, and low-cost. This study employs a juridical-empirical approach, using data gathered through interviews, observations, and literature review. The findings indicate that the online justice system, implemented with the aim of expediting the legal process, has been well received by the community, and has proven to be highly efficient in the Kendal and Semarang Religious Courts. Overall, this research highlights the importance of E-Court implementation in delivering fast, simple, and low-cost for the community, while acknowledging the need for continued efforts to enhance the system's accessibility and inclusivity.